Line positions in the v6=1 band of methyl iodide: Validation of the C3v TDS package based on the tensorial formalism. (April 2016) - Haykal, I.; Doizi, D.; Boudon, V.; El Hilali, A.; Manceron, L.; Ducros, G.
Abstract: A tensorial formalism adapted to the case of symmetric-top molecules has been recently developed in Dijon (El Hilali et al., J Quant Spectrosc Radiat Transf 2010;111, 1305–1315) [18]. It is based on the O ( 3 ) ⊃ C ∞ v ⊃ C 3 v group chain and allows a systematic expansion of the Hamiltonian and dipole moment operators, including all possible interactions for a given rovibrational polyad system. This suite of programs is used to analyze and simulate the mid-infrared spectrum of methyl iodide in order to test its performance. The v6 fundamental band has been recorded using the FTIR Bruker HR125 at the AILES beamline of the SOLEIL Synchrotron facility with the Globar internal source. 3882 lines up to J =61 were assigned and fitted with only 16 tensorial parameters. Abstract : Highlights: A line position assignment of the v 6 of methyl iodide is done. A validation of the C 3v TDS package of the XTDS suite of programs based on the tensorial formalism is proved. A further improvement of the C 3v TDS package is proposed in order to include hyperfine structure effects.